(untitled) (Indian Journal of Public Health Research & Development, 2022)
Background: Although age-standardised rates of stroke mortality have decreased worldwide, overall stroke burden has significantly increased over the last two and half decades especially in developing countries. Objectives: To predict the functional recovery of upper limb potential after acute ischemic stroke. Methods: 51 people were recruited and studied. SAFE, NIHS Score, Median nerve SSEP, Conventional MRI brain imaging are done for all 51 patients. 40 patients were cooperative for further DTI neuroimaging & FA value analysis done within 1wk of stroke onset. Standard care & rehabilitation given. Followed up for upper limb recovery with ARAT scores at 1st, 2nd & 3rd months. Clinical, electrophysiological and neuroimaging recovery variables of upper limb were analyzed between two groups. Results: FA asymmetry index of posterior limb of internal capsule (PLIC) suggest more structural asymmetry of PLIC and poor recovery. There is a significant negative correlation between fractional anisotropy asymmetry index and ARAT III score. Correlation coefficient (r) is -0.319. Conclusion: With initial simple clinical assessment scales most of the recovery can be predicted and thereby patient expectations can be managed and use effective targeted rehabilitation strategies, time & resources to bring the best outcome